Identifying and Ranking of Features and Characteristics of Online Consultation Pages and Virtual Prescription Applications with a Focus on Nutrition and Exercise - Abbasnezhad, Mohammad; irandoust, khadijeh; Hashemi, Seyed Abbas (AI and Tech in Behavioral and Social Sciences, 2024)
The objective of this study was to systematically assess and rank the features and characteristics of online consultation pages and virtual prescription applications, with a particular focus on their offerings in nutrition and exercise. The study aimed to identify which attributes of these digital health solutions most significantly influence user engagement and satisfaction, thereby guiding the optimization of such platforms for improved health management. Utilizing a qualitative research design, this study combined semi-structured interviews with 40 participants and a thorough review of 102 Instagram pages and applications related to nutrition and exercise. Participants comprised a diverse group including page users and academic experts. The data collection focused on aspects such as the presence and quality of workout and nutrition plans, availability of physical consultation options, and the involvement of recognized experts in the field. Data analysis involved coding and thematic analysis to identify and rank the key features and characteristics deemed most valuable by users. The analysis revealed a preference for online platforms that facilitate effective and direct communication with users, offering diversified content across different sports disciplines and providing services tailored to the specific needs of men and women. The inclusion of specialized teamwork, featuring collaboration among healthcare professionals, also emerged as a critical aspect. These preferences underscore the importance of personalization, interactivity, and credibility in digital health solutions catering to nutrition and exercise. This study highlights the essential features that digital health platforms should embody to enhance the management of non-communicable diseases and promote overall wellness through nutrition and exercise. The findings emphasize the necessity for digital solutions to prioritize user-centric communication, offer varied and personalized content, and engage multidisciplinary experts to meet user needs effectively.